CONCEPTUAL METAPHORS IN GENDERBASED-PROVERBS IN GERMAN AND UZBEK LANGUAGES - Bahora Juraholova Kurbonboyevna (Western European Studies, 2025)
This article focuses on the gender-specific portrayal of men and women in Uzbek and German proverbs within the framework of gender linguistics. At the core of the study is the analysis of linguistically encoded gender stereotypes, which originate from cultural and societal norms. It is demonstrated that in both cultures, women are frequently associated with attributes such as domesticity, emotionality, and submissiveness, while men are portrayed with qualities such as strength, rationality, leadership, and responsibility. The study illustrates how gender-specific role models are transmitted and subconsciously perpetuated through conceptual metaphors like “WOMAN – OBJECT” or “MAN – PILLAR.” The research highlights the need for a deeper comparative analysis of phraseological units and proverbs in the context of gender linguistics to gain insight into socially embedded patterns of thought and behavior. An interdisciplinary approach is adopted, combining cognitive, sociocultural, and linguistic perspectives
Keywords: Genderlinguistik; Geschlechterstereotype; Sprichwörter; Vergleichende Linguistik